수막재배시설 실내공기 중 라돈 농도 특성에 관한 연구 - 김상철; Sang-cheol Kim; 박찬주; Chan-ju Park; 최재혁; Jae-hyuk Choi; 서민아; Min-a Seo; 엄진균; Jin-gyun Eom; 박미선; Mi-sun Park (환경분석과 독성보건, 2021)
The aim of this study was to investigate indoor radon concentration in the water curtain cultivation facilities located in the rural area of Sejong city during the winter season. The bedrock of the southern part of the city is mainly composed of granite rocks, which have been reported to retain higher radon content than sedimentary and metamorphic rocks. The measured indoor radon concentrations were very high in all the facilities partially exceeding the recommended values provided in the 「Indoor Air Quality Control Act」 guidelines. Furthermore, we observed that operation of equipment to maintain stable indoor temperatures resulted in diurnal variations in radon concentration. Based on the results, we concluded that suitable measures such as changing the time at which work starts or ventilating in advance could help reduce the duration of exposure to radon. KCI Citation Count: 0